Game made in heaven and hell - Abd Razak, Dzulkifli (2006)
AT last, the World Cup has ended. Now life can return to normal.Though, for some, the hype may linger a while. But what is important is that we can derive valuable lessons from the competition, not that Malaysia would be in the World Cup anytime soon. Indeed, some have alluded that life is one big football match. Each of us wants to score our goals so that we can be recognised as being a success in life. And, theoretically, we have a chance to do so. As they say, the ball is round and it depends on the skill we have to handle it in our own league, advancing a step at a time. Otherwise, how else can we explain the participation of so many from the "less developed" countries, relative to Asia — purportedly, the dynamo of the world economy?